2021
DOI: 10.17275/per.21.60.8.3
|View full text |Cite
|
Sign up to set email alerts
|

Examination of University Students' Fear of Negative Evaluation and Academic Dishonesty Tendencies

Abstract: The aim of this study is to examine the relationship between university students' fear of negative evaluation and their academic dishonesty tendencies and to compare them in terms of various variables. The sample of the study carried out in the relational screening model consists of 306 students, who were selected by the easily accessible sampling method among the university students studying at Yozgat Bozok University, Turkey in the academic year 2019-2020. "Personal Information Form", "Academic Dishonesty Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, we see that fraud studies in educational institutions are still rarely carried out. The studies of fraud in schools place more emphasis on academic cheating [6], [7]. In addition, studies that examine financial fraud place more emphasis on business organizations [8]- [10] and non-business organizations other than educational institutions [11]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, we see that fraud studies in educational institutions are still rarely carried out. The studies of fraud in schools place more emphasis on academic cheating [6], [7]. In addition, studies that examine financial fraud place more emphasis on business organizations [8]- [10] and non-business organizations other than educational institutions [11]- [13].…”
Section: Introductionmentioning
confidence: 99%
“…A study with 357 undergraduates by Megan et al (2019) found that the chance of participating in academically dishonest behaviours was predicted by social rational orientation and perceived course value. Bozdağ (2021) demonstrated that students' academic dishonesty inclinations rise as their fear of bad assessments from instructors and professors grows. Subjective standards, which were found to be the largest predictor of academic dishonesty, and dishonesty were shown to be positively associated with perceived behavioural control (Maloshonok & Shmeleva, 2019;Zhang, Yin, & Zheng, 2018) were two major factors influencing students' engaging in academic dishonesty.…”
Section: Introductionmentioning
confidence: 99%
“…Pride for one's tribe relies heavily on each member's contribution, and success or failure tends to be public as a collective people. Members of the tribe feel pressure to succeed and fear being publicly shamed if unsuccessful (Bozdag, 2021). For Saudi 56 20201030 Arabian students in higher education, the fear of failure would result in failure for their families and the tribe.…”
Section: Characteristicsmentioning
confidence: 99%
“…Saudi Arabia has free public universities that follow an eastern teaching philosophy and unsubsidized private universities that have recently adopted a western teaching philosophy (Hassan & Jamaludin, 2010). Saudi Arabian students who are unprepared for success in a western-style university might go to great lengths to appear successful and avoid the shame of failure (Bozdag, 2021).…”
Section: Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation